Efficacy and safety of acupuncture treatment as an adjunctive therapy after knee replacement: Single-center, pragmatic, randomized, assessor blinded, pilot study. Issue 10 (12th March 2021) - Park, Tae-Yong; Kim, Hye-Jung; Lee, Jin-Hyun; Sunwoo, Yun-Young; Do, Kwang-Sun; Han, Seong-Nim; Song, Yun-Kyung; Chae, Dong-Sik
Abstract: Introduction: Total knee replacement (TKR) is a surgical procedure that is being increasingly performed as a result of population aging and the increased average human life expectancy in South Korea. Consistent with the growing number of TKR procedures, the number of patients seeking acupuncture for relief from adverse effects, effective pain management, and the enhancement of rehabilitative therapy effects and bodily function after TKR has also been increasing. Thus, an objective examination of the evidence regarding the safety and efficacy of acupuncture treatments is essential. The aim of this study is to verify the hypothesis that the concurrent use of acupuncture treatment and usual care after TKR is more effective, safe, and cost-effective for the relief of TKR symptoms than usual care therapy alone. Methods/design: This is an open-label, parallel, assessor-blinded randomized controlled trial that includes 50 patients with TKR. After screening the patients and receiving informed consent, the patients are divided into two groups (usual care + acupuncture group and usual care group); the patients will then undergo TKR surgery and will be hospitalized for 2 weeks. The patients will receive a total of 8 acupuncture treatments over 2 weeks after surgery and will be followed up at 3, 4, and 12 weeks after the end of the intervention. The primary outcome is assessed using the Korean version of the Western Ontario and McMaster Universities Arthritis Index (K-WOMAC), and the secondary outcome is measured using the Numerical Rating Scale (NRS), Risk of Fall, and Range of Motion (ROM). Moreover, the cost per quality-adjusted life years (QALYs) is adopted as a primary economic outcome for economic evaluation, and the cost per NRS is adopted as a secondary economic outcome. Ethics and dissemination: This trial has received complete ethical approval from the Ethics Committee of Catholic Kwandong University International St. Mary's Hospital (IS17ENSS0063). We intend to submit the results to a peer-reviewed journal and/or conferences. Trial registration: ClinicalTrials.gov Identifier: NCT03633097. Abstract : Supplemental Digital Content is available in the text